Caribbean imperatives : regional governance and integrated development - Hall, Kenneth (Ian Randle KingstonJM, 2005)
Addresses issues such as the conception of the Caribbean Community; integration theory; the exercise of sovereignty; the Single Market and Economy; production integration; the external relations of the Community; and, the importance of multilateralism for the viability of small states in the international system.